Life Cycle Assessment (LCA) of Two Different Oyster (Crassostrea gigas) Farming Strategies in the Sacca di Goro, Northern Adriatic Sea, Italy - Daniela Summa; Edoardo Turolla; Mattia Lanzoni; Elena Tamisari; Giuseppe Castaldelli; Elena Tamburini (Resources, 2023)
The Pacific oyster Crassostrea gigas is one of the world’s most cultivated and prized molluscs. Although it is usually considered a luxury product, it meets all the requirements to be included in a sustainable diet, and its production and consumption have great potential for growth in the coming years. Oyster farming is a worldwide activity, with China and France as the main producers, but recently, the possibility of implementing the Italian production, mainly focused on clams and mussels, has been considered an interesting issue, especially due to the growing local and global demand. The present study has been carried out by collecting data from the Sacca di Goro, north-east Italy, the most important national mollusc farming area. Life cycle assessment (LCA) methodology was applied to two different farming scenarios in order to improve the overall sustainability of the process. Using OpenLCA™ software (GreenDelta, Berlin, Germany) and the ReCiPe® midpoint (H) v.1.12 method, the environmental impacts of the traditional Italian farming technique, carried out entirely offshore in longlines, and the alternative option, in which the oyster seed pre-fattening phase was carried out in the lagoon, were calculated and compared. The results show that replacing the current pre-fattening phase with pre-fattening in a lagoon reduces CO2 emissions by approximately 12% and all other impact categories by approximately 9%. In addition, non-recyclable plastic materials and fuel consumption emerged as the main environmental hotspots.